PERENCANAAN PERLUASAN PELAYANAN TPST KARTOHARJO KAB. NGANJUK - Tuhu Agung Rahmanto; Yoga Romanda (EnviroUS, 2022)
The volume of waste is directly proportional to the increase in population. Thus, the level of public consumption used in daily life for materials also increases. The more waste generated, the need for land expansion. Currently, TPA Kedungdowo receives waste residue from TPST Kartoharjo in 2020 amounting to 497,655 Kg/year. This study aims to make a Service Expansion Plan for TPST Kartoharjo Kab. Nganjuk. The waste generated by the Kartoharjo TPST is 32683 kg/day. With the number of Sukomoro District as much as 6941 kg/day, Nganjuk District as much as 17648 kg/day, Bagor District as much as 8094 kg/day. The land area used for the expansion of the TPST is 1048.76 m2 .